2019
DOI: 10.3389/fneur.2019.00537
|View full text |Cite
|
Sign up to set email alerts
|

Internally Guided Lower Limb Movement Recruits Compensatory Cerebellar Activity in People With Parkinson's Disease

Abstract: Background: Externally guided (EG) and internally guided (IG) movements are postulated to recruit two parallel neural circuits, in which motor cortical neurons interact with either the cerebellum or striatum via distinct thalamic nuclei. Research suggests EG movements rely more heavily on the cerebello-thalamo-cortical circuit, whereas IG movements rely more on the striato-pallido-thalamo-cortical circuit ( 1 ). Because Parkinson's (PD) involves striatal dysfunction, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 75 publications
(102 reference statements)
0
24
0
Order By: Relevance
“…49 Increase in CLR activation during the APA task after ARTI may indicate restored automaticity in freezers. 50 Although studies demonstrated that gait 51 and internally guided lower-limb movement 52 in PD required increased activation in CLR and the cerebellum, respectively, may be because of lack of automatic control from the basal ganglia. Evidence shows that both pathological and compensatory processes in the cerebellum could play a role in PD gait.…”
Section: Discussionmentioning
confidence: 99%
“…49 Increase in CLR activation during the APA task after ARTI may indicate restored automaticity in freezers. 50 Although studies demonstrated that gait 51 and internally guided lower-limb movement 52 in PD required increased activation in CLR and the cerebellum, respectively, may be because of lack of automatic control from the basal ganglia. Evidence shows that both pathological and compensatory processes in the cerebellum could play a role in PD gait.…”
Section: Discussionmentioning
confidence: 99%
“…These findings further emphasize the involvement of brain regions implicated in visuospatial processing, information integration and attention during walking and coordination of gait. 23,24 Recent studies have highlighted the role of higher cortical brain regions during walking. For example, it was shown that increased activations in frontal, sensory, and motor brain regions in PD patients are associated with gait adaptability during treadmill walking.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ability to image changes in the basal ganglia and other brain regions associated with Parkinson’s disease remains limited (cf. 61, 62, 66, 67 ), without any such data we are forced to speculate on the neuroanatomical substrates involved. These results suggest that investigations incorporating the balance testing approaches used here in addition to neuroimaging approaches are warranted.…”
Section: Discussionmentioning
confidence: 99%